Intermittent fasting decreases oxidative stress parameters in Wistar rats (Rattus norvegicus) - Nurmasitoh, Titis; Utami, Shindy Yudha; Kusumawardani, Endah; Najmuddin, Abdulhalim Ahmad; Fidianingsih, Ika (Universa Medicina, 2018)
BackgroundChronic and degenerative diseases are closely related to modern lifestyles that tend to be deficient in physical activity but excessive in food intake. One method used to overcome this problem is dietary restriction through intermittent fasting. Intermittent fasting decreases the risk of chronic and degenerative diseases, e.g. by lowering oxidative stress. Oxidative stress can be determined from the malondialdehyde (MDA) levels and lipid profile in the blood. The present study aimed to determine the effect of intermittent fasting on plasma MDA levels and lipid profile of Wistar rats (Rattus norvegicus).MethodsThis research was a laboratory experimental research using a post test control group design. Twenty four male Wistar rats (Rattus norvegicus) were randomly assigned to 4 groups, ie control group (C), fasting group (F), non-fasting obese group (NFO), and fasting obese group (FO). Fasting treatment given in this research was intermittent fasting, comprising one day of fasting for 12 hours alternating with one day of normal feed ad libitum in the span of 8 weeks. After completion of treatment, blood was taken transcardially for examination of MDA levels and lipid profiles using spectrophotometry.ResultsThere were significant between-group differences in MDA levels and lipid profiles (p<0.05 for all parameters). Groups treated with intermittent fasting had lower levels of MDA, total cholesterol, triglycerides, and ow-density lipoprotein (LDL) than those without intermittent fasting. The high-density lipoprotein (HDL) levels were higher in the intermittent fasting group than the other groups.ConclusionIntermittent fasting has an effect on the oxidative stress parameters of Wistar rats (Rattus norvegicus).